2005
DOI: 10.1303/aez.2005.185
|View full text |Cite
|
Sign up to set email alerts
|

How does the ectoparasitoid wasp Euplectrus separatae (Hymenoptera: Eulophidae) recognize a suitable oviposition site on the host larva Pseudaletia separata (Lepidoptera: Noctuidae)?

Abstract: The larval ectoparasitoid of Pseudaletia separata, Euplectrus separatae oviposits exclusively on the dorsolateral surface from the 3rd thoracic to the 2nd abdominal segment of the host. Larval parasitoids are well known to be exposed to risks from aggressive defense behavior when they attempt to parasitize a host. E. separatae female sting the host to inject a venom prior to oviposition. At this time the female wasp is exposed to a serious risk from aggressive host behavior. However, the female avoids the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Additionally, S. cincticeps touch their prey with their antennae and legs, supporting the idea that predatory stink bugs also use tactile clues in prey selection. Similar observations have been made by others to support the conclusion that predators may use tactile (Lemos et al 2005), visual (Haynes et al 2002;Nakamatsu & Tanaka 2005) and chemical clues (Haynes et al 2002;Mendel et al 2004;Mochizuki & Yano 2007) to locate and recognize their prey. We noticed that initial recognition of the prey may directly influence the attack behavior of S. cincticeps, suggesting that it is able to adapt its behavior according to the prey being offered (Wignall & Taylor 2009).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Additionally, S. cincticeps touch their prey with their antennae and legs, supporting the idea that predatory stink bugs also use tactile clues in prey selection. Similar observations have been made by others to support the conclusion that predators may use tactile (Lemos et al 2005), visual (Haynes et al 2002;Nakamatsu & Tanaka 2005) and chemical clues (Haynes et al 2002;Mendel et al 2004;Mochizuki & Yano 2007) to locate and recognize their prey. We noticed that initial recognition of the prey may directly influence the attack behavior of S. cincticeps, suggesting that it is able to adapt its behavior according to the prey being offered (Wignall & Taylor 2009).…”
Section: Discussionsupporting
confidence: 80%
“…The parasitoid Euplectrus separatae Kamijo (Hymenoptera, Eulophidae) oviposits in areas of the body of the prey Pseudaletia separata (Walk.) (Lepidoptera, Noctuidae), which are less susceptible to defense reaction, thereby avoiding the removal of eggs and young stages of the parasitoid (Nakamatsu & Tanaka 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Thrashing can be a powerful counterattack to avoid contact with ovipositors, and may even result in dislodging or injuring parasitoids in some larvae ( Myers & Smith, 1978 ; Stamp, 1982 ; Heinz & Parrella, 1989 ). On the other hand, remaining motionless can also be an effective defense against parasitoids ( Richerson & Deloach, 1972 ; Rotheray, 1981 ), for in some parasitoid species visual cues from moving larvae are necessary for a successful oviposition ( Nakamatsu & Tanaka, 2005 ; Yamamoto, Chau & Maeto, 2009 ). Our observation that M. pulchricornis spent longer host-handling time and had an overall lower likelihood of stinging than did M. mediator The suggestion that M. separata is more effective to defense against attacks by M. pulchricornis than by M. mediator may partly explain why M. separata is less often parasitized by M. pulchricornis ( Jiang et al, 2011 ) than by M. mediator ( Li et al, 2006b ; Luo et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among many parasitoid wasps of free-living insects living on foliage, the necessity of host movement for oviposition behavior has been firmly demonstrated in a braconid parasitoid (Dinocampus coccinellae) of aphidophagous coccinellid adult beetles (Richerson and De Loach, 1972) and in an eulophid parasitoid (Euplectrus separatae) of Mythimna larvae (Nakamatsu and Tanaka, 2005). Host motion is not essential to the oviposition behavior of many braconid aphid parasitoids Mackauer, 1994, 1995), and is less important than chemical cues in an ichneumonid parasitoid (Campoletis sonorensis) of Heliothis larvae (Wilson et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Host motion has been well demonstrated to be essential for host searching and successful oviposition in polyphagous tachinid parasitoids, i.e., Exorista spp. (Stireman, 2002;Yamawaki et al, 2002;Yamawaki and Kainoh, 2005); however, only a few studies have suggested the necessity of host movement for oviposition behavior in hymenopteran parasitoids (Richerson and De Loach, 1972;Nakamatsu and Tanaka, 2005). Host motion seems to be less important or not necessary in many parasitoid wasps, even when attacking exposed-living hosts (Wilson et al, 1974;Sato, 1988;Mackauer, 1994, 1995;Demas et al, 2002).…”
Section: Introductionmentioning
confidence: 99%